2020
DOI: 10.1080/13880209.2020.1859553
|View full text |Cite
|
Sign up to set email alerts
|

Roots and stems of Kadsura coccinea extract induced developmental toxicity in zebrafish embryos/larvae through apoptosis and oxidative stress

Abstract: Context: Although the roots and stems of Kadsura coccinea (Lem.) A. C. Smith. [Schisandraceae] are herbs and traditional foods in Li nationality, its toxicity remains unclear.Objective: To study developmental toxicity of K. coccinea consumption and explain underlying mechanisms. Materials and methods: Zebrafish were applied to assess LC 50 values of hydroethanol extract (KCH) and water extract (KCW) of Kadsura coccinea. In further study, three concentrations groups of KCH (3.75, 7.5 and 15 lg/mL for embryo, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…GsME-treated zebrafish embryos exhibited significantly smaller eyes than untreated embryos (p < 0.05) in a dosage-dependent manner when compared against control groups. Previous investigations have also reported similar finding (Xia et al 2020).…”
Section: Effect On Zebrafish Eye Sizesupporting
confidence: 76%
“…GsME-treated zebrafish embryos exhibited significantly smaller eyes than untreated embryos (p < 0.05) in a dosage-dependent manner when compared against control groups. Previous investigations have also reported similar finding (Xia et al 2020).…”
Section: Effect On Zebrafish Eye Sizesupporting
confidence: 76%
“…A triagem de potenciais candidatos a terapias alternativas (utilizando produtos naturais) e/ou medicamentos, são realizadas desde os primórdios da pesquisa clínica, através de modelos experimentais, especialmente, de roedores (ratos e camundongos), Majoritariamente, pode-se observar que a principal utilização do modelo Zebrafish tem sido para avaliar toxicidade de novos compostos ou produtos naturais candidatos para aceitação regulatória (MOURA et al, 2019;SARASQUETE et al, 2018;HALLARE et al, 2014;GEBRELIBANOS et al, 2019;ALMEIDA et al, 2020;VECIANA et al, 2014;SAID et al, 2020;XIA et al, 2020;VEEREN et al, 2020;TEIXEIRA et al, 2020;CHANDRAMOHAN et al, 2019). Testes de toxicidade remetem ao estudo da capacidade de uma substância em causar danos aos organismos vivos, geralmente associada a concentração e duração da exposição, que envolve uma cascata de eventos relacionados a mecanismos de interação com órgãos-alvo, projetando efeitos nocivos que se manifestam se o xenobiótico atingir concentrações suficientes para desencadear algum efeito tóxico (MOURA et al;CHANDRAMOHAN et al, 2019;VEEREN et al, 2020).…”
Section: Atividade Biológica De Produtos Naturais Em Ensaios Pré-clín...unclassified
“…were observed in larvae treated with KCH (K. coccinea hydroethanol extract) (15 or 30 μg/ml) (Xia et al, 2020). Another in vivo study using zebrafish has reported that honokiol-induced oxidative effect is related to the dosage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Glycosides of Tripterygium wilfordii had significant impacts on reproduction‐related genes, such as Y chromosome micro‐deletion‐related gene Dzip1, germ cell apoptosis‐related gene Fas and signal transduction‐related gene Wnt4, damaging reproductivity in vivo (Zhang, Huang, et al, 2012). A hydroethanol extract of Kadsura coccinea activated genes that regulate developmental hepatotoxicity, oxidative stress and apoptosis in zebrafish, such as Bax, p53 and caspase‐3 (Xia et al, 2020). Honokiol induced developmental toxicity in the embryo via down‐regulating mRNA expression of SOD‐1, SOD‐2, cat, HO‐1 and Nrf2 (Li, Zhang, et al, 2019).…”
Section: Possible Biomarkers Of Tcm‐induced Reproductive Toxicitymentioning
confidence: 99%
See 1 more Smart Citation